Role of management accounting in controlling system of gas exploration enterprises - Фадєєва, І. Г.; Гринюк, О. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Interpretation of definition of «management accounting» by foreign and our scientists is given in the article, grouping of definitions is implemented in three directions. On the basis of a critical analysis of the conducted walkthrough of interpretations within the system approach to the definition of «management accounting» own formulation of this category has been proposed. The consideration of management accounting as a part of the information base, which provides functioning of management system of oil and gas companies stipulated research of external and internal informative environment of such enterprises and place of management accounting among other systems of financial information. On the basis of the conducted analysis the structure of the system of management accounting of oil and gas companies is worked out.